Understanding the Nexus of Human Resource Management and Financial Management: A Literature Review Perspective in Accounting - Sasongko, Budi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study explores the nexus between Human Resource Management (HRM) and Financial Management (FM) within the domain of accounting, aiming to elucidate its implications for organizational performance and financial reporting. Employing a qualitative literature review methodology, the research systematically identifies, analyzes, and synthesizes relevant scholarly works to provide a comprehensive understanding of this integration. The study's objectives are to investigate the alignment of HRM practices with financial objectives, examine the implications for financial reporting and disclosure, and propose future research directions. Through systematic search strategies and data collection techniques, diverse perspectives, theories, and empirical findings are synthesized to develop a coherent narrative. The thematic analysis reveals significant insights: firstly, strategic alignment of HRM practices with financial objectives positively impacts organizational performance, as evidenced by studies on high-performance work systems and talent management. Secondly, the integration of HRM and FM extends beyond operational performance to influence financial reporting practices and governance mechanisms, as explored in research on human resource accounting and earnings management. Finally, the study identifies future research directions, emphasizing the need for longitudinal studies, interdisciplinary research, and exploration of ESG considerations. The findings contribute to scholarly understanding by highlighting the strategic importance of aligning HRM practices with financial objectives and implications for financial reporting. Keywords: Human Resource Management, Financial Management, Accounting, Organizational Performance, Financial Reporting.